Chinese American transnationalism : the flow of people, resources, and ideas between China and America during the exclusion era - Chan, Sucheng (Asian American history and culture., 2006)
The third volume in a trilogy that offers the most comprehensive account to date of the Chinese American experience during the exclusion era.